KONTRIBUSI POTONGAN HARGA TERHADAP PENJUALAN PADA LIANCO MANDIRI COORPORATE (LMC)-LIANCO GROUP TAPANULI SELATAN - Rahmat RAHMAT S.E.,M.M (Institut Pendidikan Tapanuli Selatan, 2018)
This study aims to determine whether there is influence of discounts on sales. The formulation of the problem in this research is whether there is any effect of price discount on sales at Lianco Mandiri Coorporate (LMC) -Lianco Desa Marisi Kecamatan Angkola Timur Tapanuli Selatan.. Currently many times popping fertilizer brands with various types, benefits, design, good quality and competitive price. For companies engaged in the fertilizer industry this is a business opportunity to master market share. To face the competition, the company will do various types of pemasaraan and in a company will not be separated from the consumer, but producers must also observe the consumer behavior is always changing the time, and what consumers want in the future.Tests on the effect of price discount on dolomite fertilizer sales by using simple regression formula (using SPSS 11.5) are: Y = a + bX + e That is calculated using SPSS program. 11, 5. After all data inserted into the formula based on the results of calculations done by the writer, then obtained the value of r arithmetic <r table with dk 30-2 = 28 and t arithmetic = 0.74 and ttable = 2.048. From the results of the analysis it turns out if the price cuts up then the sales go up and if otherwise discount the price down then the value of sales also fell. Thus the hypothesis accepted the reason the value of discounts affect sales. Lianco Mandiri Coorporate (LMC) -Lianco Group Desa Marisi Kecamatan Angkola Timur Tapanuli Selatan.